Promotion of healthy eating: a study with a group of adolescents and families (Research, Society and Development, 2022)
Studies reveal that the eating habits of Brazilian adolescents and their families are unhealthy, and that promotion developed at this stage of life can favor the adoption of a healthier lifestyle during adulthood. The present work aimed to describe the development and implementation of an educational intervention aimed at promoting healthy eating for adolescents and their families, through a qualitative research, guided by the Pedagogy of the Oppressed. Data collection took place through semi-structured interviews with seven adolescents and their families, where they participated in four meetings for intervention and evaluation of an educational action. The analysis of the Collective Subject Discourse highlighted two themes, one related to the consumption of ultra-processed foods and the other about the perception of adolescents and families after the health promotion action. It was concluded that before the intervention, the adolescents and their families consumed too much ultra-processed foods, such as sausages, stuffed cookies, sweets and fried foods, after the dialogic meetings as elements of intervention, the evaluation was positive, showing a reflection for attitudinal and behavioral changes. such as: a reduction in the intake of inappropriate foods and an increase in the consumption of healthy foods, such as fruits and vegetables.